Influence of Digital Competencies and AI Usage in Enhancing Teachers’ Instructional Effectiveness in Southern Pakistan - Majeed, Muhammad Kashif; Badariah Ahmad, Tunku (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2026)
This study investigates how digital competencies and the use of Artificial Intelligence (AI) influence the instructional effectiveness of secondary school teachers in Southern Pakistan. A quantitative research approach was employed, collecting data from 440 teachers selected through purposive sampling across four tehsils in Kot Addu District. Structured questionnaires measured digital competencies, AI usage, and teacher effectiveness, and the data were analyzed using SPSS v27 with descriptive statistics, regression analysis, t-tests, and ANOVA. Results indicate that while digital competencies alone did not produce a statistically significant independent effect (p = 0.051), AI usage had a strong positive impact on teaching outcomes (p = 0.000). The combination of digital competencies and AI integration significantly improved instructional effectiveness (p = 0.024), classroom management, and student engagement. Descriptive analysis showed above-average confidence in AI and digital tools, with variations across tehsils and genders. Reliability and validity tests (Cronbach’s alpha > 0.87, Pearson correlation > 0.189) confirmed the robustness of the findings. Based on these results, the study recommends AI-focused teacher training programs, integration of digital tools into lesson planning, provision of equitable access to technology, and regular professional development. Policymakers are advised to strengthen digital infrastructure, promote AI literacy, and support lifelong learning to enhance teacher effectiveness and advance 21st-century education in Southern Pakistan.